Evaluation of Danger Dissemination Activities for Non-Procedural Indonesian Migrant Workers to Students of SMA Negeri 2 Wonosobo - Muhammad Taufiq Akbar Fitriyanto; Wilonotomo Wilonotomo (Polteknik Imigrasi, 2020)
The purpose of this outreach activity is to provide information about the practices of Indonesian Migrant Workers Non-Procedural which threaten the safety of prospective Indonesian Migrant Workers. Threats can arise mainly because of the illegal status of the migrant worker who does not obtain a job through the proper procedures stipulated in the applicable regulations. This illegal status makes these workers very vulnerable to improper treatment by employers and other parties because they know that the workers' existence is not protected by their country and is against the applicable law.